2018
DOI: 10.1590/0102-672020180001e1392
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bacteriobilia in Patients Undergoing Elective Colecystectomy

Abstract: Background: Cholelithiasis is one of the diseases with greater surgical indication. Currently, laparoscopic cholecystectomy is the gold standard in the treatment of cholelithiasis. Aim: To analyze the culture of bile from patients with cholelithiasis, mainly in the occurrence of brown and mixed stones. Methods: Was carried out a prospective study with 246 cases with biliary lithiasis who underwent elective laparoscopic cholecystectomy. Bile culture was performed in all. During anesthetic induction the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 13 publications
3
7
0
5
Order By: Relevance
“…In our study, we found a relationship between old age and bactibilia. We found that an age of ≥70 years was a risk factor for bactibilia (HR, 2.874; P = 0.001) and it was consistent with another previous study [ 14 ]. Based on several reports that human immunity decreases with aging, which increases susceptibility to infection, old age can be considered a risk factor for bactibilia [ 15 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found a relationship between old age and bactibilia. We found that an age of ≥70 years was a risk factor for bactibilia (HR, 2.874; P = 0.001) and it was consistent with another previous study [ 14 ]. Based on several reports that human immunity decreases with aging, which increases susceptibility to infection, old age can be considered a risk factor for bactibilia [ 15 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…La bacteriobilia o infección bacteriana del líquido biliar es causante de patologías de la vía biliar, como la colecistitis y la colangitis 8 . Se calcula que 22 % de la población occidental tiene litiasis biliar, y entre 13 % y el 22 % de estos pacientes desarrollará síntomas 9 .…”
Section: Discussionunclassified
“…Según los hallazgos presentados y la literatura revisada, se encuentra que a pesar de la falta de consenso sobre el uso de la terapia antimicrobiana en los pacientes con colecistitis aguda, las guías de manejo Tokio 2018 sugieren el uso profiláctico de antibiótico en pacientes que tengan riesgo moderado de severidad o la posibilidad de presentar complicaciones 21 , por otro lado, se debe tener en cuenta la toma de cultivos de bilis para la aplicación de un adecuado esquema antimicrobiano enfocado a los diferentes aislamientos microbiológicos, así como es necesario enfocar el manejo hacia los perfiles de sensibilidad y resistencia de cada institución 8 .…”
Section: Discussionunclassified
“…Culture-based studies report bacteria in 9% to 54% of patients with gallstone disease without infection ( 5 , 6 ), with the prevalence of gram-negative bacteria, Escherichia sp., Klebsiella sp. and Enterobacter sp., which account for 60.4% of the isolated bacteria ( 5 , 7 ).…”
Section: Introductionmentioning
confidence: 99%